Romanticism and animal rights - Perkins, David, 1928- (Cambridge University Press, 2003)
In England in the second half of the eighteenth century an unprecedented amount of writing urged kindness to animals: from sermons and encyclopedias to the work of the great Romantic poets. Romanticism and Animal Rights shows how English Romantic writing took up issues of what we now call animal rights.
Keywords: English literature -- 19th century -- History and criticism.; Animals in literature.; English literature -- 18th century -- History and criticism.; Animal welfare -- Great Britain -- History -- 18th century.; Animal welfare -- Great Britain -- History -- 19th century.; Animal rights -- Great Britain -- History -- 18th century.; Animal rights -- Great Britain -- History -- 19th century.; Human-animal relationships in literature.; Romanticism -- Great Britain.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Animaux dans la littérature.; Littérature anglaise -- 18e siècle -- Histoire et critique.; Animaux -- Droits -- Grande-Bretagne -- Histoire -- 18e siècle.; Animaux -- Droits -- Grande-Bretagne -- Histoire -- 19e siècle.; Relations humain-animal dans la littérature.; Romantisme -- Grande-Bretagne.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Animal rights; Animal welfare; Animals in literature; English literature; Human-animal relationships in literature; Romanticism; Great Britain; 1700-1899; Criticism, interpretation, etc.; History